The Concept of Ikumen Based on the Yokai Context of Medama Oyaji in Shigeru Mizuki's Anime Gegege No Kitaro - Rhamadani, Kristanto Eka; Wahyuddin, Zida (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
The concept of Ikumen is a concept of fatherhood in modern Japan as a father who takes care of children, enjoys taking care of children, takes care of children while working and in his care can also mature himself. The emergence of Ikumen is a turning point in the declining role of fathers in Japan over time. The purpose of this study is to describe the concept of Ikumen with different contexts in general, namely a father who is not a human being but, in his actions, can be called an Ikumen according to Moteki, Ikumen Project, Kobe Ikumen Executive, Oyama. The approach used is the sociology of literature which explains literature as a reflection of society that discusses the extent to which the literary genre used can represent all elements of society. The results of this study show that the character Medama Oyaji can portray aspects of Ikumen, namely as a man who takes care of children, enjoys childcare, takes care of children while working, and in his care is able to mature himself, which is applied through the context of yokai. Thus, this study contributes to expanding the understanding of the concept of Ikumen not only limited to human fathers, but can also be applied to representations of fathers in unique popular culture contexts such as yokai characters, thus enriching the study of fatherhood in modern Japanese society.